Belgischer Symbolismus zum Be/Greifen nah. Museumskoffer zum Werk von Léon Spilliaert und George Minne.
Der belgische Symbolismus wurde in den letzten Jahrzehnten neu entdeckt. Während Künstler wie Léon Spilliaert und George Minne lange ein Geheimtipp waren, ziehen sie nun ein großes Publikum in ihren Bann. Dennoch gelten viele Werke dieser Kunstströmung bis heute aufgrund der sie prägenden anspruchsvollen Formensprache, verborgenen Bedeutungen und mystischen Visionen als ebenso anziehend wie unergründlich. Die hier vorgestellten siebzehn Museumskoffer bieten vielfältige Zugänge, sie in ihrem kulturellen und kunsthistorischen Kontext zu entdecken und zu verstehen: Sie machen kulturelles Lernen zu einem ganzheitlichen Erlebnis und öffnen Türen zu neuen Welten. Ergänzend stellt der Katalog Texte zum Medium ‚Museumskoffer‘, zum belgischen Symbolismus und weiteres relevantes Informationsmaterial zur Verfügung.
Keywords: Belgischer Symbolismus; Museumskoffer; León Spilliaert; George Minne

31 Sprachbildung im berufsbezogenen Mathematikunterricht. - Prediger, Susanne; Wessel, Lena (Berufs-und Fachsprache Deutsch in Wissenschaft und Praxis)

Implementation of Different Communication Structures for a Rocket Chip Based RISC-V Grid of Processing Cells - Luchterhandt, Lars; Nellius, Tom; Beck, Robert; Dömer, Rainer; Kneuper, Pascal; Müller, Wolfgang; Sadiye, Babak (MBMV 2024 - 27. Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen“)
RISC-V has received worldwide acceptance in the industry and by the academic community. As of today, multiple RISC-V applications and variants are under investigation for embedded IoT systems, from resource-limited single-core processors up to multi-core systems for High-Performance Computing (HPC). Recently, the Grid of Processing Cells (GPC) platform has been proposed as a scalable parallel grid-oriented network of processor cores with local memories. This paper describes a prototype design of the GPC platform for hardware implementation at Register-Transfer Level (RTL) based on modified RISC-V Rocket processors with scratchpad memories. It introduces a scalable Chisel-based implementation of the modified Rocket cores with RTL generation and a functional test using Verilator simulation. This work also includes the adaptation of the Chipyard software toolchain to extend the compiler to multi-core grids with different local address spaces.

A Scalable RISC-V Hardware Platform for Intelligent Sensor Processing - Palomero Bernardo, Paul; Schmid, Patrick; Bringmann, Oliver; Iftekhar, Mohammed; Sadiye, Babak; Müller, Wolfgang; Koch, Andreas; Jentsch, Eyck; Sauer, Axel; Feldner, Ingo; Ecker, Wolfgang (DATE 24 - Design Automation and Test in Europe)

„Wir wollen mitreden!“ – Entwicklung und Validierung von Skalen zur Erfassung motivationaler Regulation bei der Teilnahme an Befragungen zur Evaluation des Studiums (SMR-Eval) - Koppenborg, Markus; Klingsieck, Katrin B. (Zeitschrift für Pädagogische Psychologie)
Zusammenfassung: Für die Evaluation und Qualitätsentwicklung von Studium und Lehre werden häufig quantitative Befragungen von Studenten eingesetzt. Jedoch ist häufig unklar, aus welcher Motivation Studenten an den Befragungen teilnehmen und inwieweit unterschiedliche motivationale Regulationsstile mit dem Antwortverhalten im Fragebogen zusammenhängen. Ausgehend von der Selbstbestimmungstheorie der Motivation nach Deci und Ryan stellt der Beitrag die Entwicklung der Skalen zur motivationalen Regulation bei Befragungen zur Evaluation (SMR-Eval) vor. Studie 1 zeigt die fünffaktorielle Struktur des Instruments. Studie 2 weist auf eine starke Messinvarianz bezüglich Geschlecht, Abschlussziel und Fakultät hin. Korrelationen mit Drittvariablen belegen die konvergente Validität der fünf Subskalen. In Studie 3 werden latente Profilanalysen über die fünf Regulationsstile berechnet. Die Ergebnisse zeigen vier Profile, welche sich inhaltlich plausibel im Antwortverhalten der Befragten unterscheiden und damit Hinweise auf die Kriteriumsvalidität der Skalen geben. Diskutiert werden theoretische und praktische Implikationen für Evaluationsvorhaben an Hochschulen sowie Übertragungsmöglichkeiten auf andere Evaluationsgegenstände.
Keywords: Developmental and Educational Psychology

The association between dairy intake in adolescents with inflammation and risk markers of type 2 diabetes during young adulthood – results of the DONALD study - Hohoff, E; Jankovic, N; Perrar, I; Schnermann, ME; Herder, C; Nöthlings, U; Libuda, Lars; Alexy, U (Public Health Nutrition)
ABSTRACT OBJECTIVE: The aim of this analysis was to investigate whether habitual intake of total dairy (TD) or different dairy types (liquid, solid, fermented, not-fermented, low-fat, high-fat, low-sugar and high-sugar dairy) during adolescence is associated with biomarkers of low-grade inflammation as well as risk factors of type 2 diabetes in young adulthood. DESIGN: Multivariable linear regression analyses were used to investigate prospective associations between estimated TD intake as well as intake of different types of dairy and a pro-inflammatory score, based on hsCRP, IL-6, IL-18, leptin and adiponectin, and insulin resistance assessed as HOMA2-IR in an open cohort study. SETTING: Dortmund, Germany PARTICIPANTS: Data from participants (n=375) of the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were included, for whom at least two 3-day weighed dietary records during adolescence (median age: 11 years) and one blood sample in young adulthood (>18 years) were available. RESULTS: There was no statistically significant association between TD intake or intake of any dairy type and the pro-inflammatory score (all p>0.05). TD intake as well as each dairy type intake and insulin resistance also showed no association (all p>0.05). CONCLUSIONS: The habitual intake of dairy or individual types of dairy during adolescence does not seem to have a major impact on low-grade systemic inflammation and insulin resistance in the long term. There was no indication regarding a restriction of dairy intake for healthy children and adolescents in terms of diabetes risk reduction.
Keywords: Public Health; Environmental and Occupational Health; Nutrition and Dietetics; Medicine (miscellaneous)

Modular 3D roller straightening – A new approach to straightening and forming of spring steel wires (X10CrNi18-8) - Dahms, Frederik Simon; Homberg, Werner (Materials Research Proceedings)
Abstract. Spring steel wires are usually supplied and stored on coils. The manufacturing and coiling processes of these wires induce inhomogeneous plastic deformations that lead to undesirable residual stresses and varying wire curvatures in the semi-finished product. These residual stresses and curvatures defects are causing varying process conditions in the subsequent manufacturing processes, which have a negative impact on the product quality, leading to wastage and thus affecting the economic and ecological efficiency. Especially the curvature deviations must be compensated for the stability of the subsequent processes. This is usually realised with roller straighteners, which are set manually by the machine operators only at the beginning of a process. In this paper, we introduce a new approach with a modular straightening-machine design and a new set-up process. The more isolated deformation behaviour in a module-based straightener overcomes the complexity of interactions between the close-positioned spaced straightening rollers. This is combined with a set-up process that is independent of conventional material testing, modelling the actual and batch-specific behaviour of the wire in the straightening process. The exact knowledge and time-consuming determination of the material properties thus becomes obsolete. The experimental investigations show the influence of defined straightening strategies on the residual stress evolution and the residual forming limit of the spring steel wires (X10CrNi18-8) in the new straightening process.

Geodesic Interpolation of Frame-Wise Speaker Embeddings for the Diarization of Meeting Scenarios - Cord-Landwehr, Tobias; Boeddeker, Christoph; Zorilă, Cătălin; Doddipatla, Rama; Haeb-Umbach, Reinhold (ICASSP 2024 - 2024 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Noctua 2 Supercomputer - Bauer, Carsten; Kenter, Tobias; Lass, Michael; Mazur, Lukas; Meyer, Marius; Nitsche, Holger; Riebler, Heinrich; Schade, Robert; Schwarz, Michael; Winnwa, Nils; Wiens, Alex; Wu, Xin; et al. (Journal of large-scale research facilities)
Noctua 2 is a supercomputer operated at the Paderborn Center for Parallel Computing (PC2) at Paderborn University in Germany. Noctua 2 was inaugurated in 2022 and is an Atos BullSequana XH2000 system. It consists mainly of three node types: 1) CPU Compute nodes with AMD EPYC processors in different main memory configurations, 2) GPU nodes with NVIDIA A100 GPUs, and 3) FPGA nodes with Xilinx Alveo U280 and Intel Stratix 10 FPGA cards. While CPUs and GPUs are known off-the-shelf components in HPC systems, the operation of a large number of FPGA cards from different vendors and a dedicated FPGA-to-FPGA network are unique characteristics of Noctua 2. This paper describes in detail the overall setup of Noctua 2 and gives insights into the operation of the cluster from a hardware, software and facility perspective.
Keywords: Noctua 2; Supercomputer; FPGA; PC2; Paderborn Center for Parallel Computing

Visual Tracking Nonlinear Model Predictive Control Method for Autonomous Wind Turbine Inspection - Amer, Abdelhakim; Mehndiratta, Mohit; le Fevre Sejersen, Jonas; Pham, Huy Xuan; Kayacan, Erdal (2023 21st International Conference on Advanced Robotics (ICAR))

Analysis and Simulation of a Photonic Multiband FMCW Radar Sensor System using Nyquist Pulses - Kruse, Stephan; Schwabe, Tobias; Kneuper, Pascal; Kurz, Heiko G.; Meinecke, March-Michael; Scheytt, Christoph (German Microwave Conference (GeMiC))

Phase Noise Analysis of Photonic Radar Systems with Optical LO Distribution - Kruse, Stephan; Kneuper, Pascal; Schwabe, Tobias; Kurz, Heiko G.; Meinecke, Marc-Michael; Gonzalez-Huici, María A.; Scheytt, J. Christoph (nternational Conference on Microwaves for Intelligent Mobility (ICMIM))

Doppler Analysis of a Lidar-Photonic Radar Combined Sensor System - Kruse, Stephan; Brockmeier, Jan; Kneuper, Pascal; Schwabe, Tobias; Kurz, Heiko G.; Meinecke, Marc Michael; Scheytt, J. Christoph (International Radar Symposium (IRS))

Inverses Verfahren zur Identifikation piezoelektrischer Materialparameter unterstützt durch neuronale Netze - Koch, Kevin; Claes, Leander; Jurgelucks, Benjamin; Meihost, Lars; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

Einfluss der periodischen Struktur auf geführte Wellen in gewebeverstärkten Polymeren - Claes, Leander (Fortschritte der Akustik - DAGA 2024)

Beschreibung des akustischen Verhaltens verklebter plattenförmiger Strukturen mittels Kopplungsmodellen - Zeipert, Henning; Hölscher, Jonas; Claes, Leander; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

On the repulsion effect of coupled Lamb wave modes - Nicolai, Marcel; Bulling, Jannis; Lugovtsova, Yevgeniya; Zeipert, Henning; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

SootUp: A Redesign of the Soot Static Analysis Framework - Karakaya, Kadiray; Schott, Stefan; Klauke, Jonas; Bodden, Eric; Schmidt, Markus; Luo, Linghui; He, Dongjie (Tools and Algorithms for the Construction and Analysis of Systems)
Abstract Since its inception two decades ago, Soot has become one of the most widely used open-source static analysis frameworks. Over time it has been extended with the contributions of countless researchers. Yet, at the same time, the requirements for Soot have changed over the years and become increasingly at odds with some of the major design decisions that underlie it. In this work, we thus present SootUp , a complete reimplementation of Soot that seeks to fulfill these requirements with a novel design, while at the same time keeping elements that Soot users have grown accustomed to.

UNav-Sim: A Visually Realistic Underwater Robotics Simulator and Synthetic Data-Generation Framework - Amer, Abdelhakim; Álvarez-Tuñón, Olaya; Uğurlu, Halil İbrahim; Le Fevre Sejersen, Jonas; Brodskiy, Yury; Kayacan, Erdal (2023 21st International Conference on Advanced Robotics (ICAR))

Modellierungen außerinstitutioneller Aneignungsprozesse digital-materieller Interfaces und (musik-)pädagogische Anschlüsse - Neuhausen, Timo; Ahlers, Michael (Musik – Digitalisierung – Bildung)